1984
DOI: 10.1111/j.1476-5381.1984.tb10762.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of auto‐inhibitory feed‐back in cardiac sympathetic transmission assessed by simultaneous measurements of changes in 3H‐efflux and atrial rate in guinea‐pig atrium

Abstract: 1 Guinea-pig right atria were labelled with [3H]-noradrenaline or [3H1-dopamine before superfusion in a flow-cell. Choice of label did not significantly alter either the relationship between 3H-efflux and number of electrical field pulses or the inhomogeneity of labelling. 2 The relationship between 3H-efflux and frequency of 4 field pulses (0.125 -2 Hz) was hyperbolic and similar to the tachycardia-frequency relationship measured simultaneously. No evidence was found for a U shaped 3H-efflux-frequency relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Ramiprilat by itself did not modify the stimulation-induced release of radioactivity. Discussion It has been concluded from in vivo experiments that Ang II increases the release of norepinephrine in the heart 23 ; the effect has also been demonstrated directly in isolated heart tissues. 1426 The present results are in line with previous studies that have demonstrated a 50% increase of transmitter release by 10" 8 mol/L Ang II in guinea pig atria, 12 a doubling by 3xl0~7 mol/L in rat atria, 13 and a 50% increase by 10" 8 to 10" 7 mol/L in mouse atria.…”
Section: Effects Of Angiotensin Imentioning
confidence: 99%
“…Ramiprilat by itself did not modify the stimulation-induced release of radioactivity. Discussion It has been concluded from in vivo experiments that Ang II increases the release of norepinephrine in the heart 23 ; the effect has also been demonstrated directly in isolated heart tissues. 1426 The present results are in line with previous studies that have demonstrated a 50% increase of transmitter release by 10" 8 mol/L Ang II in guinea pig atria, 12 a doubling by 3xl0~7 mol/L in rat atria, 13 and a 50% increase by 10" 8 to 10" 7 mol/L in mouse atria.…”
Section: Effects Of Angiotensin Imentioning
confidence: 99%
“…However, our conclusions are not based on the determination of 3H overflow (as in most experiments of Story and coworkers), but on the overflow of [3H1-noradrenaline. In our view, 3H overflow that was increased by field stimulation in an organ bath containing electrodes and tissue holder, but no biological tissue (Angus et al, 1984; Figure 1) does not represent a presynaptic parameter as reliable as the authentic labelled transmitter itself. In this context, it was important to show that the overflow of [3H]-noradrenaline from the organ bath was not increased by field stimulation in the absence of atria (Figure 1).…”
Section: Discussionmentioning
confidence: 70%
“…We adopted similar, though not identical methodology to that described by McCulloch et al (1974) which was used in the paper reporting the lack of muscarinic inhibition by acetylcholine (Story et al, 1975 (Illes et al, 1984). Such an increase could be due to current-induced tissue damage as suggested by Illes et al (1984), but may in part be due to displacement of 3H-compounds (other than noradrenaline) from plastic, glass, or metal surfaces (Angus et al, 1984). The results obtained in the presence of Tyrode solution (cocaine, corticosterone, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In guineapig right atria, phentolamine has no effect on tachycardia or 3H-efflux in response to 1-4 field pulses under conditions where no autoinhibition occurs (Angus & Korner, 1980;Angus et al, 1983). Similarly, phentolamine does not significantly alter the blood pressure in conscious ganglion-blocked guinea-pigs (Lew & Angus, unpublished).…”
mentioning
confidence: 99%